Emulation of the subjective experience of visual dorsal stream dysfunction: a description of three in depth case studies - St Clair Tracy, Helen; McDowell, Nicola; Dutton, Gordon N.; Ravenscroft, John; Hay, Isobel; Blaikie, Andrew (Frontiers in Human Neuroscience, 2025)
These case studies explore the subjective visual experiences of individuals with cerebral visual impairment (CVI), specifically dorsal stream dysfunction (DSD) characterized by simultanagnosia. Through three in-depth case studies, this work documents the challenges these individuals face when navigating cluttered environments. The individuals were asked to describe their visual experiences while watching videos of varying complexity, with the future aim of creating a simulation of simultanagnosia. This process revealed a dynamic constriction of their attentional visual fields as scene complexity increased, and vice versa. Notably, the volunteers experienced a phenomenon where their vision could “get stuck” on specific items, with an apparent concurrent reduction in their ability to perceive and describe visual information as visual clutter increased. These consistent observations indicate that the symptoms of simultanagnosia are not simply limited to perceiving one or two objects at a time but can vary dynamically in response to environmental complexity. They enhance our understanding of how DSD impacts visual search and perceptual experiences, prompting us to propose the term “simultanagnostic vision” to describe this more nuanced and dynamic manifestation of CVI. The results are critical for developing effective interventions and optimizing support strategies for individuals affected by DSD, particularly children at sensitive developmental stages. Furthermore, we recommend deeper investigation into how different visual processing streams in the brain interconnect and influence each other, which may open new avenues for targeted therapeutic interventions.